SISTEMA DE EJERCICIOS PARA EL DESARROLLO DE LA RESISTENCIA A LA VELOCIDAD ANAERÓBICA DE CORTA DURACIÓN DE VELOCISTAS CATEGORÍA JUVENIL DE FEDERIOS. - ROBERTIZ MORA DAYANA ELOISA (2024)
Planning your exercise system is essential, as goals are achieved through proper programming to achieve the right load at optimal anaerobic speed. It is important to know that the preparation is beneficial for sprinters who follow the same general rules every day. In this research process the main problem is posed: What is the incidence of a system of exercises for the development of resistance to the anaerobic speed of short duration of Federios youth category sprinters? The research is crucial to identify and establish the appropriate exercises to increase endurance and increase anaerobic speed, which will result in high performance athletes. The objective is to determine the incidence of a system of exercises for the development of short-duration anaerobic speed endurance in Federios youth category sprinters. This research work has a mixed quali-quantitative methodological approach. It is complemented with documentary, field, descriptive and documental research. It is concluded that different aspects such as maximum effort always contribute to the development of anaerobic endurance. However, their progress was not considered significant because they had not strengthened their legs to achieve an adequate development. The connection between anaerobic endurance and speed of athletes allows a slightly deeper analysis and with a specialized approach to both topics, from the studies conducted and the results obtained, it is possible to generate some arguments that suggest that it contributes to include important elements that need to be socialized.